2015
DOI: 10.1108/jgm-06-2014-0023
|View full text |Cite
|
Sign up to set email alerts
|

Till stress do us part: the causes and consequences of expatriate divorce

Abstract: Purpose -International relocation is undoubtedly a source of stress for families, and in particular for married couples. Yet, despite familial challenges and the fact that "family concerns" remain a top reason for assignment refusal and assignment failure, including a growing body of anecdotal evidence suggesting that many expatriate marriages fail often at huge cost to organizations, there is not one academic study yet published on expatriate divorce. The purpose of this paper is to empirically examine the ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
57
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(60 citation statements)
references
References 64 publications
2
57
1
Order By: Relevance
“…While sojourning is unique to a specific environment, the overall experiences among sojourning families in foreign countries might overlap in areas. These include unfamiliarity with local practices, language barriers, and separation of extended family members (Erogul & Rahman, ; McNulty, ). The results of this study have insights for agencies that serve immigrants and sojourner populations as well as company training programs.…”
Section: Recommendations and Implicationsmentioning
confidence: 99%
“…While sojourning is unique to a specific environment, the overall experiences among sojourning families in foreign countries might overlap in areas. These include unfamiliarity with local practices, language barriers, and separation of extended family members (Erogul & Rahman, ; McNulty, ). The results of this study have insights for agencies that serve immigrants and sojourner populations as well as company training programs.…”
Section: Recommendations and Implicationsmentioning
confidence: 99%
“…Previous research has shown that migration is often associated with elevated psychosomatic problems (Carballo et al, 1998;Al-Baldawi, 2002), reduced well-being (Liebkind and Jasinskaja-Lahti, 2000), elevated depression levels (Bhugra, 2004), and increased drug and alcohol use (Polednak, 1997;Caetano and Clark, 2003). Apart from being detrimental to the migrants themselves, these adverse effects on mental health related outcomes also have negative downstream consequences for existing spouses and family members of migrants, for potential organizations that have hired these migrants, and for society at large (Mäkelä and Suutari, 2013;Selmer and Lauring, 2014;McNulty, 2015). Therefore, if acculturation improves migrant happiness this would be an important issue (Marsiglia et al, 2013).…”
Section: Acculturation and Well-being Of Migrantsmentioning
confidence: 99%
“…For example, while a range of organisational, national cultural and individual factors contributing to lack of gender balance amongst expatriates have been well examined within the literature (see Hutchings & Michailova, 2017;Shortland, 2009), McNulty and, other areas of individual difference are less examined (e.g. lesbian, gay, bisexual and transgender [LGBT] expatriates -see Gedro [2010] and McPhail, McNulty, and Hutchings [2016]: cited in McNulty and ; and single parent and split families -see McNulty [2015]: cited in McNulty and Hutchings [2016]). Given the uncertainty involved in living and working in a foreign country, unsurprisingly the roles of: commitment to the parent organisation, the host organisation and task performance; individual differences; the level of social support available; and, situational stressors; have all been examined as contributors to expatriate adjustment and assignment success (see Kraimer & Wayne, 2004).…”
Section: Expatriates and The Employment Relationshipmentioning
confidence: 99%